(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The kidneys play a key role in maintaining a constant internal environment. This is achieved by regulating body fluid volumes and their content in various dissolved substances, including electrolytes and various products of metabolism. With declining kidney function, these functions are wholly or partially lost. The result is a difficulty in volume regulation and the accumulation of various substances in supra-physiological concentrations. This study included(42 patient with renal failure ) that compared with 42 healthy control groups, this study was conducted in the dialysis center of Al-Rifai General Hospital in Al-Rifai city. The result of this study shown the there was a highly significant P- Value (<0.001) increase of urea in patient groups(mean±SD= 107±35.5)than control group (mean±SD= 32.5±6.36). the there was a highly significant P- Value (<0.001) increase of creatinine in patient groups(mean±SD= 5.45±2.40)than control group (mean±SD= 0.724±0.200).In this study concluded that urea increase in patients compare with control in highly significant. Highly significant appear in high creatinine with patients compare to control. Ages of patients and control are close and that display not there any relation between ages and Kidney failure